Pengaruh Praktik Human Capital Performance Management (HCPM) dan Work Engagement terhadap Peningkatan Kinerja Pegawai Swasta Generasi Z di Kota Bima - Jaenab; Sugeng Widakdo; Mulyadin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The purpose of this study is to determine the simultaneous positive and significant influence of Human Capital Performance Management (HCPM) and work engagement on the performance of Generation Z employees in Bima City. This research employs a quantitative approach. The type of research used is associative, with the population consisting of all private-sector Generation Z employees in Bima City. The sample includes 100 Generation Z employees selected through purposive sampling based on specific criteria. The research instrument used is a questionnaire with a Likert scale. The data analysis technique applied in this study is multiple linear regression analysis using SPSS version 21. The results of the study show that: (1) Human Capital Performance Management (HCPM) has a positive and significant effect on the performance of Generation Z employees in Bima City; (2) Work engagement has no positive and significant effect on the performance of Generation Z employees in Bima City; and (3) Human Capital Performance Management (HCPM) and work engagement jointly have a positive and significant effect on the performance of Generation Z employees in Bima City